Rationale and design of a multicenter randomized clinical trial of vestibulodynia: understanding pathophysiology and determining appropriate treatments (vestibulodynia: UPDATe). (31st December 2022) - Carey, Erin T.; Geller, Elizabeth J.; Rapkin, Andrea; Farb, Debbie; Cutting, Haley; Akaninwor, Jasmyn; Stirling, Christopher; Bortsov, Andrey; McNulty, Steven; Merrill, Peter; Zakroysky, Pearl; DeLaRosa, Jesse; et al.
Abstract: Background: Limited data are available to establish evidence-based management protocols for vestibulodynia (VBD), a chronic vulvar pain condition that affects approximately 14 million women in the U.S. For the purposes of the study, our group subdivided VBD subtypes that may benefit from different types of treatment: 1) VBD peripheral (VBD-p), characterized by pain localized to the vulvar vestibule and 2) VBD central (VBD-c), characterized by VBD alongside one or more other chronic overlapping pain conditions (e.g. irritable bowel syndrome, temporomandibular disorder, and fibromyalgia syndrome) that affect remote body regions. Here, we describe the rationale and design of an NIH-funded multicenter clinical trial comparing the effectiveness of topical and/or systemic medication for alleviating pain and normalizing pain- relevant biomarkers among women with VBD-p and VBD-c. Methods: Participants will be randomly assigned to one of four parallel arms: peripheral treatment with 5% lidocaine + 0.5 mg/ml 0.02% oestradiol compound cream + oral placebo pill, 2) central treatment with the tricyclic antidepressant nortriptyline + placebo cream, 3) combined peripheral cream and central pill treatments, or 4) placebo cream and placebo pill. The treatment phase will last 16 weeks, with outcome measures and biomarkers assessed at 4 time points (0, 8, 16, and 24 weeks). First, we will compare the efficacy of treatments in alleviating pain using standardized tampon insertion with a numeric rating scale and self-reported pain on the short form McGill Pain Questionnaire. Next, we will compare the efficacy of treatments in improving perceived physical, mental, and sexual health using standardized questionnaires. Finally, we will measure cytokines and microRNAs in local vaginal and circulating blood samples using multiplex assays and RNA sequencing, and determine the ability of these biomarkers to predict treatment response. Conclusion: This is the first multicenter randomized controlled trial to evaluate the efficacy of peripherally and centrally acting medications currently used in clinical practice for treating unique VBD subtypes based on distinct clinical and biological signatures. Administrative information: Vestibulodynia UPDATe is a multi-centre, two-by-two factorial designed randomized, double-blind, placebo-controlled trial registered at clinical trials.gov (NCT03844412). This work is supported by the R01 HD096331 awarded to Drs. Nackley, Rapkin, Geller and Carey by the Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD). Key messages: Peripheral lidocaine and oestradiol and centrally-targeted nortriptyline medications are used for the treatment of pain in women with VBD, but there is a lack of data from well-powered RCTs. This two-by-two factorial RCT will test the efficacy of these medications in VBD subtypes characterized by distinct clinical characteristics and biomarker profiles. We hope that results will provide clinicians with scientific evidence of therapeutic efficacy in distinct VBD subtypes in an effort to direct and optimize treatment approaches.